Karakterisasi Ekstrak Spon Laut Axinella carteri Dendy Secara Fisika, Kimia Dan Fisikokimia - Harrizul Rivai; Meliyana Meliyana; Dian Handayani (STIFARM Padang, 2010)
Characterization of the liquid extract of marine sponge (Axinella carteri Dendy) has been carried out by using the physical, chemical and physicochemical methods. The physical character of the extract was yellowish brown liquid, smells fishy and bitter taste, with a specific gravity of 0.9644 ± 0.02576. The marine sponge contained alkaloids, steroids and terpenoids, with total alkaloid content of 0.9433% ± 0.136133%. In physicochemical analysis, residu on drying was 7.156% ± 0.2944%, ash content 2.5576% ± 0.2668%, acid insoluble ash 0.014% ± 0.0035%, concentration of substances dissolved in water 5.6153% ± 0.2759%, concentration of substances dissolved in ethanol was 6.4263% ± 0.4622%, levels of a substance extracted from each fraction was 0.9066% ± 0.0666% in hexane fraction, 0.1866% ± 0.03045% in chloroform fraction, 0.0616% ± 0.04297% in ethyl acetate fraction and 6.449% ± 0.07642% in water fraction. Profile of thin layer chromatography (TLC) showed the existence five stain with value Rf 0.1; 0.16; 0.3; 0.44 and 0.56.